Electronic, Structural and Vibrational Properties of GaP Diamondoids and Nanocrystals: A Density Functional Theory Study - Mudar Ahmed Abdulsattar; Bahjat B. Kadhim; Huda M. Jawad (Nanomaterials and Nanotechnology, 2015)
The electronic, structural and vibrational properties of gallium phosphide diamondoids and nanocrystals were investigated using density functional theory at PBE/6-31(d) level, which included polarization functions. The energy gap obeyed the quantum confinement size effect with shape fluctuations. The gap converged towards its bulk limit at 2.26 eV. The Ga-P bond lengths of higher diamond‐ oids were found to be distributed around the bulk experi‐ mental value at 2.36 Angstrom. Tetrahedral angles were found around the ideal bulk zincblende value at 109.47, degrees while dihedral angles were distributed around the ideal bulk zincblende values at ±60 and ±180 degree. These findings illustrate that diamondoids are a good represen‐ tative of bulk structure. An analysis of vibrational modes, in terms of reduced masses, force constants and IR intensi‐ ty, was then performed. The size-related change of certain vibrational frequencies of GaP diamondoids was compared with the experimental bulk. Radial breathing mode frequency began from 187 cm-1 for the smallest molecule GaPH6 and decreased with fluctuations, heading to 0 cm-1 as its bulk limit. Longitudinal optical mode began from 187 cm-1 for the smallest molecule and increased with fluctua‐ tions, heading to 376.9 cm-1 (11.3 THz) as its bulk limit. Hydrogen-related vibrations were relatively constant and can therefore be used to identify GaP diamondoids because of their high IR and Raman intensity peaks.